Polar codes for some multi-terminal communications problems - Sahebi, Aria G.; Pradhan, S. Sandeep (Proceedings / IEEE International Symposium on Information Theory, 2014)
It is shown that polar coding schemes achieve the known achievable rate regions for several multi-terminal communications problems including lossy distributed source coding, multiple access channels and multiple descriptions coding. The results are valid for arbitrary alphabet sizes (binary or non-binary) and arbitrary distributions (symmetric or asymmetric).